ENVIRONMENTAL BENCHMARKING FOR LOCAL AUTHORITIES - Marinela GHEREŞ; Alexandra GOGOZAN (Management & Marketing, 2010)
This paper is an attempt to clarify and present the many definitions ofbenchmarking. It also attempts to explain the basic steps of benchmarking, toshow how this tool can be applied by local authorities as well as to discuss itspotential benefits and limitations. It is our strong belief that if cities useindicators and progressively introduce targets to improve management andrelated urban life quality, and to measure progress towards more sustainabledevelopment, we will also create a new type of competition among cities andfoster innovation. This is seen to be important because local authorities’actions play a vital role in responding to the challenges of enhancing thestate of the environment not only in policy-making, but also in the provision ofservices and in the planning process. Local communities therefore need tobe aware of their own sustainability performance levels and should be able toengage in exchange of best practices to respond effectively to the ecoeconomicalchallenges of the century.